Smart Strategy Synergy of Government Administration in Rogojampi Sub-District Banyuwangi Regency - Akbar Maulana; Ali Wafa; Sampir Andrean Sukoco (POLITICO, 2025)
Practicality requires bureaucrats to be more innovative and effective in leading and administering government affairs. Young & transparent access to information, digitization, and services to the public that are very serving, are important components that must be owned by government agencies at various levels. The East Java Provincial Government Administration Synergy Competition (SP2K) in 2022 is a way to test the sophistication of governance synergy at the sub-district level. Uniquely, Rogojampi won first place in the SP2K competition. This study aims to determine the strategy used by the District of Rogojampi, as a sub-district with good governance at the sub-district level. The results research can serve can be adopted for their success in order to lead to the synergy of good governance. Research shows that Rogojampi District has carried out the mandate in Government Regulation Number 17 of 2018 concerning Districts on the subject of innovation and public service well. Rogojampi as the main figure in carrying out general government tasks at the sub-district level, has carried out synergies and collaborations, so that his government practices give birth to innovations that are beneficial to the community, Rogojampi District Creative Innovation; Hacker Production House, Posting Dong, Yamin Perkasa, Pak Asmat, and GROBAKS.